Free p-Cresol Alters Neutrophil Function in Dogs - Bosco, Anelise Maria; Pereira, Priscila Preve; Martins Almeida, Breno Fernando; Narciso, Luis Gustavo; Santos, Diego Borba dos [UNESP]; Santos-Neto, Alvaro Jose dos [UNESP]; Ferreira, Wagner Luis; Ciarlini, Paulo Cesar (Wiley-Blackwell, 2016)
To achieve a clearer understanding of the mechanisms responsible for neutrophil dysfunction recently described in dogs with chronic renal failure (CRF), the plasma concentrations of free p-cresol in healthy dogs (n = 20) and those with CRF (n = 20) were compared. The degree of correlation was determined between plasma levels of p-cresol and markers of oxidative stress and function of neutrophils in these dogs. The effect of this compound on oxidative metabolism and apoptosis was assessed in neutrophils isolated from 16 healthy dogs incubated in RPMI 1640 supplemented with p-cresol (0.405 mg/L) and compared with medium supplemented with uremic plasma (50%). To achieve this, the plasma concentration of p-cresol was quantified by liquid phase high-performance liquid chromatography. The neutrophil oxidative metabolism was determined using the probes hydroethidine and 2', 7'-dichlorofluorescein diacetate and apoptosis was measured using Annexin V-PE by capillary flow cytometry. Compared with the healthy dogs, uremic dogs presented higher concentrations of free p-cresol, greater oxidative stress, and neutrophils primed for accelerated apoptosis. The free p-cresol induced in neutrophils from healthy dogs increased apoptosis and decreased reactive oxygen species production. We conclude that the health status presented during uremia concomitant with the increase in plasma free p-cresol can contribute to the presence of immunosuppression in dogs with CRF.
Keywords: Apoptosis; Respiratory burst; Superoxide; Uremia; Chronic renal failure; P-cresol